Overpopulation as a Social Catastrophe in Ireland: An Analysis of Jonathan Swift’s A Modest Proposal from the Perspective of Malthusian Catastrophe (Journal of Social Sciences Review, 2023)
The validity of Ireland’s tragedies fixes itself perfectly on the theory of Malthusian Catastrophe proposed by Thomas Robert Malthus. To prove how Ireland is driven to the Malthusian havoc rests upon proving how and why the Crown exploits the Irish and their country. That is tackled by inspecting Swift’s appeal to the government, A Modest Proposal, and convinces its audience that the ruin caused in Ireland is all in fact the blame of the Parliament, a panorama that Swift clasps onto in his essay. Swift’s claims from this literary piece are used to make explicit why he thought the British were to be blamed for the Malthusian decree of Ireland. Further, the paper meanders into the positive and preventative checks of Malthus’s doctrine aligning it with the absurd solution Swift presents in his essay. An impartial verdict regarding the so-called Ireland’s genocide conspiracy is dispensed. The reasons why Swift’s manuscript turns out a biting satire is picked apart and fiddled with. The researchers employ mammoth support from other research projects, Thomas Malthus’s own records, and also from the controversial masterpiece of Jonathan Swift’s A Modest Proposal, and have penned down a carefully formulated chronological stream of evidence that wraps in its bearings the results of the research. The matrix grid of confirmations answers how the population surge was caused in Ireland equating in a Malthusian catastrophe, how do Malthus’s checks align with Swift’s grisly solution and why was his satiric solution so unsettling.
Keywords: Ireland; Malthusian catastrophe; Positive checks; A Modest Proposal; Parliament; Satire; Population-surge